Implementation of Islamic Education Learning Using A Fun Learning Approach in Improving Student's Emotional Intelligence - Sarah, Siti; Rena, Syahidah; Pahrurraji (AN NUR: Jurnal Studi Islam, 2024)
Education is a right that must be given to every child. At this time, researchers realize that early childhood is experiencing an extraordinary process of growth and development. So, it is important for parents to direct their children's education appropriately, especially religious education. Through fun learning, it will be easier for children to carry out learning activities, so they don't feel monotonous and bored. So this research aims to implement Islamic Religious Education learning through a Fun Learning approach and its relationship to increasing students' emotional intelligence. This type of research uses qualitative descriptive research which focuses on describing how Islamic Religious Education (PAI) learning through Fun Learning can increase children's emotional intelligence. Primary data sources are documentation, interviews with the Academic Team, teachers and parents. Secondary data sources are modules, journals, articles and books. The results of the research concluded that, 1) Implementation of the Fun Learning approach in Islamic Religious Education (PAI) learning is as follows: a) making PAI learning plans for early childhood; b) through three stages of learning implementation using a Fun Learning approach and edutainment methods; c) conducting evaluations through book reports with five learning points, and 2) increasing students' emotional intelligence by: a) increasing the duration of children's learning focus, b) forming interest, c) student involvement in learning and d) growing awareness in learning.